2017
DOI: 10.3390/biomedicines5030047
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Repression of MicroRNAs Is Associated with High Guanine Content in the Terminal Loop Sequences of Their Precursors

Abstract: Widespread microRNA (miRNA) repression is a phenomenon observed in mammals after exposure to cigarette smoke and in many types of cancer. A comprehensive reduction in miRNA expression after treatment with the hormone estrogen has also previously been described. Here, we reveal a conserved association of miRNA downregulation after estrogen exposure in zebrafish, mouse, and human breast cancer cell line, with a high guanine content in the terminal loop sequences of their precursors, and offer a possible link bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…The results presented here support previous studies showing the potential importance of TL-G content to the regulation of miRNAs expression and function [19][20][21][22]. We have previously suggested that estrogens metabolites inside the lungs, as a result of CS exposure, can potentially cause the observed widespread downregulation of miRNA expression, and contribute to lung tumor development [27,28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results presented here support previous studies showing the potential importance of TL-G content to the regulation of miRNAs expression and function [19][20][21][22]. We have previously suggested that estrogens metabolites inside the lungs, as a result of CS exposure, can potentially cause the observed widespread downregulation of miRNA expression, and contribute to lung tumor development [27,28].…”
Section: Discussionsupporting
confidence: 90%
“…Repressed miRNAs in lung and breast cancers were shown to be the most enriched in TLs G [22], and the relation of estrogen to the development of these types of cancer is well documented [27,30,31]. Furthermore, like in the current study, also in the aforementioned studies, dual GG enrichment in miRNA TLs was even more pronounced [20][21][22]. Remarkably, experimental studies have shown that sequences with repeated G bases (GG or GGG) show higher reactivity toward oxidation than isolated G bases [32].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thirdly, an a priori understanding of genetic background and physiological states is equally warranted, as specific teleost strains (Burgerhout et al, 2017) or endogenous factors may factors regulate epigenetic marks in addition to environmental factors (Figure 1). The importance of endogenous factors is exemplified by the estrogen-dependent regulation of the abundant and liver specific miRNA-122 in zebrafish (Cohen and Smith, 2014;Cohen et al, 2017), which may introduce sex-specific functional differences in the nutritional regulation and metabolic function of miRNA-122 in fish (Mennigen et al, 2015). Indeed, widespread sexually dimorphic miRNA expression profiles have been identified in developing zebrafish (Vaz et al, 2015), emphasizing that genetic or endogenous endocrine signals contribute to environmental regulation of epigenetic marks in teleost fish.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…miRNA, discovered in the late 20th century, is a unique class of small RNAs derived from the non-coding DNA regions of a gene, such as intron, and 5'- and 3'-untranslated region (UTRs), which play multiple roles in cell regulation, including proliferation, differentiation, and apoptosis. Expression of this class of RNA is tightly regulated by environmental conditions, including temperature, ( 6 ) pressure, ( 7 ) hormones, ( 8 ) endotoxins ( 9 ) and environmental toxins, ( 10 ) to maintain homeostasis. Several recent studies have revealed that some phytochemicals modulate miRNA expression to exhibit their physiological functions.…”
Section: Biological Functions and Recently Identified Mechanismsmentioning
confidence: 99%